PENGARUH PENGAWASAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada Karyawan Ayam Goreng Nelongso Regional Surabaya) - Hakiki Mufarozi; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT In the development of globalization requires all companies to be more competitive. Every company must have excellence and competitiveness so that it can survive among other companies. The success of a company is also strongly influenced by human resources owned and can be seen from the performance of its employees. The purpose of this study was to find out to find out and analyze the influence of supervision on the performance of employees of Surabaya Nelongso Fried Chicken. To find out and analyze the influence of work discipline on the performance of employees of Surabaya Nelongso Fried Chicken. To describe the influence of supervision and work discipline on the performance of employees of Surabaya Nelongso Fried Chicken. With the population of this study were 150 employees. By using the Slovin formula. The sample in this study were internal employees totaling 60 employees. The results of this study are known to be positive variables but not significant or it can be concluded that the assistant variable does not effect employee performance. Work discipline variables have a positive and significant effect, or it can be concluded that the work discipline variables affect employee performance. Keywords: Supervision, Work Discipline, Employee Performance